Method for Ensuring Information Security of Object Fiber-Optical Data Transmission System - A. O. Zenevich; E. V. Novikov; T. A. Matkovskaia; A. A. Lagutik (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Currently, ensuring information security of object fiber-optic data transmission systems is an important and urgent task. Therefore, the purpose of this article is to develop an easy-to-implement method for protecting object fiber-optic data transmission systems from unauthorized access to information. This work proposes an easyto-implement method for protecting object fiber-optic data transmission systems from unauthorized access to an information signal, based on weakening the power of this signal. It is shown that the use of the proposed method will not lead to a significant decrease in the data transmission rate in the object fiber-optic data transmission systems, but will increase its information security. The theoretical limit of signal decoding for data transmission technologies over optical fiber Ethernet has been determined. It was found that the lowest value of the theoretical limit of signal decoding corresponds to Fast Ethernet technology (100Base-FX). It was found that when the value of the attenuation coefficient of optical radiation D > 20 dB, the data transmission using Fast Ethernet technology (100Base-FX) is terminated. The results of this article can find application in the means of technical protection of information transmitted over object fiber-optic data transmission systems.